Visualization and axial viewing techniques - Lecoeur,N; Zeng,YJ; Hale,CP; Hewitt,GF (Multiphase Science and Technology, 2011)
Axial viewing techniques are advanced photographic methods that have been widely used to visualize two-phase flow systems. A review of the axial viewing techniques is presented, describing the development of axial view systems from their origin to diverse variants of the original device such as the parallel-light technique, the in-line axial viewer used on the Imperial College high pressure multiphase flow rig, and the high-temperature axial viewing system. With these techniques, it has been possible to visualize in detail the various flows and to identify previously unknown mechanisms. These techniques show great continuing potential in elucidating two-phase flow phenomena. © 2011 by Begell House, Inc.